Blotto, Twinks and the conquistadors' gold - Brett, Simon (Brett, Simon. Blotto and Twinks mystery, 2023)
Blotto and Twinks are once again launched into another death-defying adventure, this time in the civil war-torn republic of Jalapeno, in Mexico. Desperate to escape her mother's match-making attempts Twinks sets out to visit her old friend, Begonia Guiteras, who lives close to an Aztec dig she wants to work on. Unfortunately, her visit coincides with the War for Jalapeno Independence, headed by Begonia's father. Twinks's excavation of the Aztec site is revealing the exciting prospect of a hoard of Conquistadors' gold - but will taking it away from the burial ground unleash the dreaded Curse of Attatotalloss? Into this confusion stumbles Blotto. On being reunited with Twinks they then discover Begonia has been kidnapped by Mexican government forces and both set out to rescue her. Will trusty chauffeur Corky Froggett, as so very often in past adventures, be able to save the day?